Pengaruh pajak daerah dan retribusi daerah terhadap peningkatan pendapatan asli daerah Kabupaten Malang - Firmansyah, Fahmi Alif; Ummah, Fitri Khoirotul; Nisa, Haliza Chafifatun; Suryati, Suryati (Maliki Interdisciplinary Journal, 2024)
In Law no. 33 of 2004 describes the management of local revenue, where this is a reflection of the implementation of regional autonomy. One that plays a role is the existence of regional taxes and regional retribution towards increasing original income in Malang Regency. This research method uses quantitative research with primary and secondary data sources. The analytical method of this study used descriptive analysis, classical assumption test, multiple linear regression analysis, determination coefficient, F test and T test to find the effect of regional income in Malang Regency. The results of this study indicate that regional taxes and regional fees have no effect on Malang's original regional income.